2009
DOI: 10.1016/j.rgg.2008.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and oxygen isotopes in the Frasnian–Famennian section of the Kuznetsk basin (southern West Siberia)

Abstract: The first detailed isotope-geochemical study of carbonate deposits has been performed in the Lower Famennian stratotype section of the northwestern Kuznetsk Basin (Kosoy Utyos), which was localized in the middle latitudes of the Northern Hemisphere in the Late Devonian. The δ13Ccarb, δ13Corg, and δ18O variation curves were constructed for the section deposits. Geochemical and petrographic studies of carbonates allowed allocation of samples that underwent postsedimentation alteration and exclude them from furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…7a-c). The δ O values of the studied shells are depleted relative to those of their modern (~ 0‰ VPDB) counterparts (Brand et al, 2003) due to the fact that the Paleozoic ocean waters were significantly depleted in 18 O compared with modern oceans but the fossil values are generally within the range documented for the global middle Devonian, particularly around Late Frasnian, in South China, Siberia, Europe and N. America Buggisch, 1993, 1996;Chen et al, 2002;Yudina et al, 2002;Joachimski et al, 2004;da Silva and Boulvain, 2008;Ma et al, 2008;Izokh et al, 2009).…”
Section: Shell Preservationmentioning
confidence: 90%
See 1 more Smart Citation
“…7a-c). The δ O values of the studied shells are depleted relative to those of their modern (~ 0‰ VPDB) counterparts (Brand et al, 2003) due to the fact that the Paleozoic ocean waters were significantly depleted in 18 O compared with modern oceans but the fossil values are generally within the range documented for the global middle Devonian, particularly around Late Frasnian, in South China, Siberia, Europe and N. America Buggisch, 1993, 1996;Chen et al, 2002;Yudina et al, 2002;Joachimski et al, 2004;da Silva and Boulvain, 2008;Ma et al, 2008;Izokh et al, 2009).…”
Section: Shell Preservationmentioning
confidence: 90%
“…Buggisch, 1993, 1996;Chen et al, 2002;Yudina et al, 2002;Joachimski et al, 2004;da Silva and Boulvain, 2008;Ma et al, 2008;Izokh et al, 2009). Although some studies utilized well preserved low-Mg calcitic brachiopod shells and phosphatic conodonts (e.g., Joachimski et al, 2004), others involved frequently whole-rock samples of variable degrees of preservation, and at times low-resolution sampling (big sampling intervals), which likely masked some significant variations around the boundary.…”
Section: Upper Frasnian Biochemostratigraphy (Namur-dinant Basin Vs mentioning
confidence: 99%
“…Many of these study sites have been strongly influenced by increased sedimentation from the rising Appalachian Mountains. Additional studies have been conducted in locations that would presumably not be affected by the Appalachian/Variscan Orogenic Events, but all are associated with sediments derived from the cratonic blocks of Indochina (Hara et al, 2010 andKönigshof et al, 2012), South China (Zheng et al, 1993, Chen et al, 2005, Gharaie et al, 2007, Chen et al, 2013, Komatsu et al, 2014and Whalen et al, 2015, Australia (Stephens andSumner, 2003 andGeorge et al, 2014), Russia/Siberia (Gutak et al, 2008, Izokh et al, 2009and Tagarieva, 2013 and northern Africa . In contrast, only one study has unequivocally shown the presence of a Late Devonian anoxia event in an open oceanic setting far from continental-derived sediments: Carmichael et al (2014) have documented the Kellwasser Event using multiple geochemical proxies within the Central Asian Orogenic Belt (CAOB), which therefore required an overhaul of the established models for ocean anoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Δ 13 C is often used as reliable paleo‐ p CO 2 barometer [ Cramer and Saltzman , 2007; Young et al , 2008], because the isotopic difference between carbonate and organic matter is dominated by photosynthetic fractionation, which partly depends on the concentration of dissolved CO 2 in seawater [e.g., Popp et al , 1989; Freeman and Hayes , 1992; Hayes et al , 1999]. Unfortunately, most previous studies focused separately on the changes of inorganic and organic carbon isotope [ McGhee et al , 1986; Joachimski and Buggisch , 1993; Wang et al , 1996; Racki et al , 2002; Xu et al , 2003; Buggisch and Joachimski , 2006; Izokh et al , 2009], few examined the variations of Δ 13 C. Even the few Δ 13 C data seem to change geographically [ Joachimski , 1997; Chen et al , 2005]. In the Baisha and Fuhe sections from south China, Δ 13 C shows high‐frequency vibrations around the F‐F boundary [ Chen et al , 2005], but it is suggested that there is no obvious change in Europe [ Joachimski et al , 2002].…”
Section: Introductionmentioning
confidence: 99%